(untitled) (The International Research Journal of Management Science, 2019)
This paper aims to examine the effect of corporate governance practice on financial performance of insurance companies in Nepal. The study used board size, number of board meetings, CEO duality, Audit committee are the explanatory variables for corporate governance. Firm size and age of the firms are considered as control variables. The dependent variable performance has been measured using Return on Assets (ROA) and return on equity ROE. The study employed descriptive cum causal relational research design. All the 23 listed insurance companies are considered as the population of the study. Only 18 insurance companies (13 non-life and 5 life) is taken as sample based on availability of data representing 78.26 % sample. The secondary data of profitability has been extracted from annual report of the company. The explanatory variables related to corporate governance has been collected through structured survey questionnaire. The study period accounts for the eight years from 2011 to 2018 with 141 firm year observations. Data has been analyzed using a multiple linear regression model. The study concludes that there exists strong relationship between the corporate governance practices and firms’ performance. The board meeting and audit committee were found to positively affect the financial performance of insurance companies. Board size is found to be negative but not significant. The study also concludes CEO duality has the negative impact on the performance of the insurance company. Firm with large in size with high board meeting tend to perform well. Age of the company also positively influenced on the financial performance of insurance companies in Nepal.